Method of Unsteady Hydrodynamic Characteristics ‎Determination in Turbulent Boundary Layer - Vasiliy Shabarov; Pavel Kalyasov; Vitaliy Shaposhnikov; Fedor Peplin (Journal of Applied and Computational Mechanics, 2021)
This paper presents the method of the turbulent flow simulation. The method may be used to address the computational aeroacoustics (CAA) problems, where the vortex noise’s sources have to be determined. This method is an alternative to both large-eddy simulation (LES) methods and stochastics turbulence simulation techniques. The proposed method is more computationally efficient compared to LES and, unlike stochastic approaches, it does not require empirical constants. The simulation according to this method is achieved in two main stages. During the first step the averaged flow’s properties are obtained using the RANS simulation. These properties are used for the formulation of the discrete vortex model on the second step. Vortices’ intensities are oscillating with amplitudes and frequencies obtained from the RANS simulation with random phase shifts. Turbulent velocity field is then determined as the sum of averaged flow velocities, velocities induced by the pulsing vortices and velocities induced by the trailing vortices (Kelvin circulation theorem). The method is verified by considering the test problem. The developed turbulent boundary layer near the horizontal wall is simulated by means of both the presented method and the LES method. A good agreement between these two methods indicates on the viability of the approach presented in this paper. However, a thorough investigation of the method is still yet to be accomplished.